Tópicos Em Nutrição E Tecnologia De Alimentos 2019
DOI: 10.22533/at.ed.71819120311
|View full text |Cite
|
Sign up to set email alerts
|

MORTADELA TIPO BOLOGNA ADICIONADA DE FARINHA DE SEMENTE DE ABÓBORA (Cucurbita maxima) COMO ANTIOXIDANTE NATURAL

Abstract: O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. 2019 Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais. www.atenaeditora.com.br Sendo assim, a SAN está relacionada a fome, a desnutrição, a obesidade, ao sobrepeso, as doenças ligadas à alimentação e à qualidade dos alimentos, ao modelo de produção e co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 66 publications
3
2
0
Order By: Relevance
“…The ash contents of the treatments were lower than those reported by Pires et al 25 . (17.4–27.5 g kg −1 ), while the protein contents corroborated the study of Chaves et al 26 . (154.5–173.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The ash contents of the treatments were lower than those reported by Pires et al 25 . (17.4–27.5 g kg −1 ), while the protein contents corroborated the study of Chaves et al 26 . (154.5–173.…”
Section: Resultssupporting
confidence: 87%
“…The ash contents of the treatments were lower than those reported by Pires et al 25 (17.4-27.5 g kg −1 ), while the protein contents corroborated the study of Chaves et al 26 (154.5-173. g kg −1 ). Concerning the fat contents, lower values were observed when compared to the findings of Pires et al 25 (∼250 g kg −1 ) and similar to those observed by Chaves et al 26 (∼200 g kg −1 ), once those authors used a higher percentage of pork back fat and mechanically separated meat, which contributes to the increase in the fat content of the Bologna sausage formulations.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations